Active Reconfigurable Intelligent Surface Enhanced Secure and Energy-Efficient Communication of Jittering UAV - Ge, Yimeng; Fan, Jiancun; Zhang, Jinbo (IEEE internet of things journal, 2023)
Unmanned Aerial Vehicles (UAVs) have emerged as a promising technology for facilitating communication in the Internet of Things (IoT), owing to their ability to provide enhanced security. However, the communication performance of UAVs can be significantly impacted by the jittering characteristics resulting from random airflow and fuselage vibration. To address this issue, a novel active reconfigurable intelligent surface (RIS) has been developed, which enables a secure and energy-efficient beamforming design. This design takes into account the effect of UAV jittering and involves joint optimization of the reflecting coefficient of the active RIS, beamforming at the UAV-borne base station, and UAV trajectory, subject to worst-case secrecy rate constraints. Unfortunately, the joint optimization problem is non-convex, making it intractable to solve. To overcome this challenge, the non-convex problem is reformulated using linear approximation and treated with linear matrix inequality using Sprocedure and Schur's complement. The problem is then decoupled into three sub-problems, including UAV trajectory, passive beamforming, and active RIS's reflecting coefficient optimization, which are solved via alternate optimization. The results of numerical simulations demonstrate that active RIS significantly enhances the power efficiency of secure UAV communication, even under the influence of UAV jitter.